The periods of maximum oscillations of the bivalve Corbula mediterranea (costa) density - Roventa, Vasile; Gomoiu, Marian Traian (Cercetări Marine - Recherches Marines, 2026)
On the basis of the mathematical method of self-correlation the multiannual periods of the maximum variations of the bivalve Corbula mediterranea density at Mamaia (Romanian Black Sea littoral) are established. These periods are: 3.1 years for Corbula populations at a depth of 4m, 11.5 years for those at a depth of 8m and 6.9 years at a depth of 12m.